Analisis Akibat Hukum dari Pengabulan Izin Poligami oleh Hakim Dengan Dalil Istri Tidak Dapat Melahirkan Keturunan Yang Tidak Disertai Surat Keterangan - Muhammad Rullie Febian Rangkuti; Hanafi Tanawijaya (UNES Law Review, 2023)
Polygamy is a legal action where a husband marries more than one woman in a marriage, which is done by submitting a request to the court in his domicile. Polygamy has several conditions to be carried out, one of which is to include a certificate that the wife has a condition that makes it impossible for her to bear children. In the decision on petition 635/Pdt.G/2023/PA.JT the judge granted the petitioner's request to practice polygamy but was not accompanied by a certificate stating that the wife could not bear children, thus causing legal uncertainty in submitting a polygamy application.